WHERE DO PHONEMES COME FROM? A VIEW FROM THE BOTTOM - Taylor, John R. (International Journal of English Studies, 2009)
Infants have a remarkable ability to perceive all manner of phonetic contrasts. The phonological categories of a language, however, have to be learned from experience. Two learning paradigms are contrasted – supervised learning (where learners receive feedback on their categorization attempts) and unsupervised learning (where learners rely only on properties of the input). It is argued that unsupervised learning may be the appropriate paradigm, at least for the initial stages of acquisition. Thereafter, the emergence of phoneme categories draws on various kinds of knowledge available to the learner, including knowledge of articulation, and of literacy conventions. A concluding section emphasizes the taxonomic nature of the phoneme, and suggests that the special salience of a phonemic representation reflects the status of the phoneme as a basic level category.